Functional Plasticity in Auditory and Visual Discrimination Processing in Patients with Single-Sided Deafness: An EEG Study. - Liu, Qiaoyu; Qiao, Yufei; Zhu, Min; Yang, Jiayan; Sun, Wen; Chen, Yaohan; Jiao, Saiyi; Shen, Hang; Shang, Yingying (Trends in Hearing, 2026)
Single-sided deafness (SSD) is a typical condition of partial auditory deprivation. Total auditory deprivation triggers cross-modal neural reorganization, but in patients with partial hearing deprivation, how residual auditory function is balanced with the compensatory plasticity of other sensory modalities remains unclear. Previous studies have reported conflicting findings, potentially due to differences in study populations or task designs. Here, we investigated hierarchical neural processing in a homogeneous cohort of 37 congenital SSD patients (31.6 ± 6.5 years, 18 males) and 32 normal-hearing (NH) controls (30.6 ± 7.3 years, 14 males) using both auditory and visual oddball tasks with electroencephalography (EEG). In the auditory task, SSD patients presented reduced amplitudes of early exogenous components (N1, P2) and mismatch negativity (MMN), but preserved late endogenous components (N2, P3), compared with NH controls. Conversely, in the visual task, SSD patients presented increased early visual N1 amplitudes with intact visual mismatch negativity (vMMN) and endogenous components (N2, P3). No latency differences in the above components were observed. These results reveal a difference in plasticity between lower- and higher-level processing. Our findings indicate that functional plasticity in SSD patients occurs predominantly at sensory stages and is characterized by diminished auditory and compensatory elevated visual neural activity, whereas higher-level discrimination processing in either modality is largely unaffected. These findings clarify prior discrepancies, establish a hierarchical framework for understanding neuroplasticity in partial sensory deprivation, and have implications for rehabilitation strategies for SSD patients.